Some Aspects of Organizing Strategic Management Accounting in Crisis Management - S. M. Bukhoriev (Учёт. Анализ. Аудит, 2018)
At the present stage of social development economic entities face various problems that threaten not only their stability in the market, but also their survival. Such problems can take many forms, ranging from financial scandals and setbacks to epidemics, natural disasters, clashes between employees and even terrorist attacks. These problems are beyond companies’ control, but when if necessary they can respond to changes in the external and internal environment. This is the case when such changes, even conditionally, fit into the strategy of their operation, and the information about such changes is submitted for making strategic management decisions in a timely manner. Strategic management accounting is a key to the readiness of a company to address the challenges of tomorrow. Strategic management accounting of today is more than merely a block of information designed for long-term planning. Strategic management accounting is primarily organizational activity which examines the environment of a company. The information collected is used to analyze the possible strategic alternatives and coordinate actions to implement them. Crisis management today is a consequence of various crisis phenomena that arise both in the external and internal environment of the company.Crisis management involves the strengthening of the company’s ability to respond to various forms of crisis flexibly and quickly. The purpose of organizational crisis management is to make timely decisions based on strategic management accounting information.